The Societal Unconscious Psychosocial Perspectives on Adult Learning - Salling Olesen, Henning (Research on the Education and Learning of Adults, 2019)
The Societal Unconscious sets a new broad horizon for in-depth understanding of learning in everyday life. The psychosocial approach re-integrates the societal and the psychodynamic dimensions in analyzing adult learners and learning processes, recognizing psychodynamic dimensions of learning. Readership: This book will be essential for scholars and advanced students working in interdisciplinary boundary zones in social and cultural sciences, education and psychology and other disciplines.